Abnormal regulation of microRNAs and related genes in pediatric β‐thalassemia. Issue 9 (16th August 2021) - Wang, Haiwei; Chen, Meihuan; Xu, Shiyi; Pan, Yali; Zhang, Yanhong; Huang, Hailong; Xu, Liangpu
Abstract: Background: MicroRNAs (miRNAs) participate in the reactivation of γ‐globin expression in β‐thalassemia. However, the miRNA transcriptional profiles of pediatric β‐thalassemia remain unclear. Accordingly, in this study, we assessed miRNA expression in pediatric patients with β‐thalassemia. Methods: Differentially expressed miRNAs in pediatric patients with β‐thalassemia were determined using microRNA sequencing. Results: Hsa‐miR‐483‐3p, hsa‐let‐7f‐1‐3p, hsa‐let‐7a‐3p, hsa‐miR‐543, hsa‐miR‐433‐3p, hsa‐miR‐4435, hsa‐miR‐329‐3p, hsa‐miR‐92b‐5p, hsa‐miR‐6747‐3p and hsa‐miR‐495‐3p were significantly upregulated, whereas hsa‐miR‐4508, hsa‐miR‐20a‐5p, hsa‐let‐7b‐5p, hsa‐miR‐93‐5p, hsa‐let‐7i‐5p, hsa‐miR‐6501‐5p, hsa‐miR‐221‐3p, hsa‐let‐7g‐5p, hsa‐miR‐106a‐5p, and hsa‐miR‐17‐5p were significantly downregulated in pediatric patients with β‐thalassemia. After integrating our data with a previously published dataset, we found that hsa‐let‐7b‐5p and hsa‐let‐7i‐5p expression levels were also lower in adolescent or adult patients with β‐thalassemia. The predicted target genes of hsa‐let‐7b‐5p and hsa‐let‐7i‐5p were associated with the transforming growth factor β receptor, phosphatidylinositol 3‐kinase/AKT, FoxO, Hippo, and mitogen‐activated protein kinase signaling pathways. We also identified 12 target genes of hsa‐let‐7a‐3p and hsa‐let‐7f‐1‐3p and 21 target genes of hsa‐let‐7a‐3p and hsa‐let‐7f‐1‐3p, which were differentially expressed in patients with β‐thalassemia. Finally, we found that hsa‐miR‐190‐5p and hsa‐miR‐1278‐5p may regulate hemoglobin switching by modulation of the B‐cell lymphoma/leukemia 11A gene. Conclusion: The results of the study show that several microRNAs are dysregulated in pediatric β‐thalassemia. Further, the results also indicate toward a critical role of let7 miRNAs in the pathogenesis of pediatric β‐thalassemia, which needs to be investigated further. Abstract : We performed microRNA sequencing to identify the microRNA expression profiling of pediatric β‐thalassemia. Totally, 530 microRNAs were identified. Based on criteria of fold change >1.5 and p ‐value <0.05, 111 microRNAs were upregulated in β‐thalassemia patients, while 85 microRNAs were downregulated in β‐thalassemia patients. Those microRNAs could clearly distinguish the normal cohorts from the β‐thalassemia patients. Hsa‐miR‐2100‐3p, hsa‐microRNA‐15a‐5p, hsa‐microRNA‐16‐5p, and hsa‐miR‐503‐5p were all downregulated in pediatric β‐thalassemia patients. We also found five let7 microRNAs hsa‐let‐7b‐5p, hsa‐let‐7i‐5p, hsa‐let‐7f‐5p, hsa‐let‐7e‐5p, and hsa‐let‐7d‐5p and were downregulated in pediatric thalassemia patients.